# Integral of arsinhx using logarithmic form?

I have came across a question which has already took a lot of my time, basically it states that I must use the relationship that arsinhx = ln (x+sqrt (x×x+1))

to integrate arsinhx.

I already know how to integrate arsinhx, but I couldn't really manage to integrate it in logarithmic form.

I tried using by parts and substitutions, but it quickly got messy and very tedious, is there a clean way to achieve this?

Relevance
• cidyah
Lv 7
6 years ago

∫ arcsinh x dx = ∫ ln ( x+ sqrt(x^2+1) ) dx

Integrate by parts

dv= dx; v= x

u = ln ( x + sqrt(1+x^2) )

du = 1 / ( x + sqrt(1+x^2) ) d/dx ( x + sqrt(1+x^2) )

du = 1 / ( x + sqrt(1+x^2) ) ( 1 + 2x / 2sqrt(1+x^2) )

du = ( 1+ x / sqrt(1+x^2) ) / ( x + sqrt(1+x^2) )

du = ( sqrt(1+x^2) + x ) / (sqrt(1+x^2) ( x+sqrt(1+x^2))

du = 1 / sqrt(1+x^2) dx

∫ u dv = u v - ∫ v du

∫ ln ( x+ sqrt(x^2+1) ) dx = x ln ( x + sqrt(1+x^2) ) - ∫ x dx / sqrt(1+x^2) ----------- (1)

Consider the integral ∫ x dx / sqrt(1+x^2)

Let u=1+x^2

du = 2x dx

x dx = (1/2) du

∫ x dx / sqrt(1+x^2) = (1/2) ∫ du/ sqrt(u) = sqrt(u) = sqrt( 1+x^2)

substitute this into (1)

∫ ln ( x+ sqrt(x^2+1) ) dx = x ln ( x + sqrt(1+x^2) ) - sqrt (1+x^2) + C

• Ian H
Lv 7
6 years ago

Use relationship that arcsinh(x) = ln[x + √(x^2 + 1)] to integrate arcsinh(x)

Let 2x = e^y – e^(-y) = 2sinh(y) …………………………(1)

so that y = arcsinh(x) = sinh^-1(x)

(e^y)^2 – 2xe^y – 1 = 0

e^y = x ± √(x^2 + 1), with e^y > 0, so that explains why

ln(e^y) = y = sinh^-1(x) = ln[x + √(x^2 + 1)] …… (2)

d/dx[ln(x)*x] = ln(x) + 1, (using the product rule)

and from that we can work out ∫ln(x)dx = xln(x) – x

We can use that approach to find the integral of (2) by asuming that

it will contain the term xln[x + √(x^2 + 1)]

d/dx{ ln[x + √(x^2 + 1)] * x} = ln[x + √(x^2 + 1)] + T, where

T = x*d/dx{ ln[x + √(x^2 + 1)]}

T = x/[x + √(x^2 + 1)] * [1 + x/√(x^2 + 1)] which rearranges as

T = x/[x + √(x^2 + 1)] * [x + √(x^2 + 1)] /√(x^2 + 1)

That looks messy until you notice that the squared bracket terms cancel.

T = x/√(x^2 + 1)] This tells us that

∫ln[x + √(x^2 + 1)]dx = xln[x + √(x^2 + 1)] - ∫[x/√(x^2 + 1)]dx

Substituting back and integrating the last term

∫arcsinh(x)dx = x*arcsinh(x) - √(x^2 + 1)

Regards – Ian H

• Nick
Lv 6
6 years ago

This will be useful:

d/dx(e^(arcsinhx)) = e^(arcsinhx)*d/dx(arcsinhx) = 1+x/(x^2+1)^(1/2) = e^(arcsinhx)/(x^2+1)^(1/2)

=> d/dx(arcsinhx) = 1/(x^2+1)^(1/2)

Now integrate by parts:

int(arcsinhx dx) = xarcsinhx - int(x/(x^2+1)^(1/2) dx)

= xarcsinhx - (x^2+1)^(1/2) + constant <----